Anatomy of stem in some Euphorbiaceae –II - A, Thakur H; Patil, D A (Journal of Experimental Sciences, 2012)
This communication includes stem anatomical characteristics of 17 species of the 17 euphorbiaceous genera. The observations pertain to the epidermis, hypodermis, cortex, vascular tissues and pith. The cell wall contours have been described in detail. Occurrence of cell inclusions is also noted in different tissues of the stem – axes. The authors are inclined to state that the anatomical features of stem axes are taxonomically significant.